Beyond the heart: a review exploring non-cardiovascular effects of vasoactive agents - Lan, Peng; Chen, Lina; Zhang, Chen; Ni, Jun; Yu, Peihao; Zhou, Jiancang (Frontiers in Pharmacology, 2025)
Vasoactive agents, traditionally recognized for their roles in cardiovascular regulation, have garnered increasing attention for their non-cardiovascular effects across various physiological systems. This review explores the multifaceted roles of vasoactive agents such as catecholamines, vasopressin, and angiotensin II beyond their cardiovascular implications. We examine the mechanisms of action, focusing on receptor interactions and the implications for various physiological systems. Key areas of impact include the central nervous system, where vasoactive agents influence mood, cognition, and neurological function, alongside potential neurotoxicity. Additionally, we discuss gastrointestinal effects, including motility and secretion, as well as renal implications related to blood flow and acute kidney injury risk. The endocrine effects are also addressed, particularly regarding insulin and glucagon secretion. Furthermore, we analyze hematological effects on coagulation and endothelial function, emphasizing the risk factors for thromboembolic events. The clinical implications of this review underscore the importance of monitoring non-cardiovascular effects in patient management and developing strategies to mitigate associated risks. Future research should focus on unraveling the detailed mechanisms of vasoactive agent-receptor interactions and their resulting organ responses, to minimize complications arising from clinical use.